An Integrated Approach to Aggregate Control for Therapeutic Bispecific Antibodies Using an Improved Three Column Mab Platform‐Like Purification Process. (17th October 2018) - Andrade, Cassia; Arnold, Lindsay; Motabar, Dana; Aspelund, Matthew; Tang, Alison; Hunter, Alan; Chung, Wai Keen
Abstract : Single chain variable fragment‐IgGs (scFv‐IgG) are a class of bispecific antibodies consisting of two single chain variable fragments (scFv) that are fused to an intact IgG molecule. A common trend observed for expression of scFv‐IgGs in mammalian cell culture is a higher level of aggregates (10%–30%) compared to mAbs, which results in lower purification yields in order to meet product quality targets. Furthermore, the high aggregate levels also pose robustness risks to a conventional mAb three column platform purification process which uses only the polishing steps (e.g., cation exchange chromatography [CEX]) for aggregate removal. Protein A chromatography with pH gradient elution, high performance tangential flow filtration (HP‐TFF) and calcium phosphate precipitation were evaluated at the bench scale as means of introducing orthogonal aggregate removal capabilities into other aspects of the purification process. The two most promising process variants, namely Protein A pH gradient elution followed by calcium phosphate precipitation were evaluated at pilot scale, demonstrating comparable performance. Implementing Protein A chromatography with gradient elution and/or calcium phosphate precipitation removed a sufficient portion of the aggregate burden prior to the CEX polishing step, enabling CEX to be operated robustly under conditions favoring higher monomer yield. From starting aggregate levels ranging from 15% to 23% in the condition media, levels were reduced to between 2% and 3% at the end of the CEX step. The overall yield for the optimal process was 71%. Results of this work suggest an improved three‐column mAb platform‐like purification process for purification of high aggregate scFv‐IgG bispecific antibodies is feasible. © 2018 The Authors. Biotechnology Progress published by Wiley Periodicals, Inc. on behalf of American Institute of Chemical Engineers. Biotechnol. Prog ., 35: e2720, 2019